PENGARUH METODE ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA SISWA DI KELAS IV SD NEGERI 34 SIMPANG HARU: PENGARUH METODE ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA SISWA DI KELAS IV SD NEGERI 34 SIMPANG HARU - Vellina Salmi; Ismira; Dini Maielfi (Jurnal Riset Pendidikan Dasar Dan Karakter, 2025)
This study aims to determine the effect of the role playing method on the speaking skills of fourth-grade students at SD Negeri 34 Simpang Haru in social studies learning. The low speaking skills of students, characterized by passive behavior, shyness, and lack of confidence, became the main background of this research. This quantitative research employed an experimental method with a one-group pretest-posttest design. The research subjects consisted of 23 students. Data were collected through speaking skills tests before and after the treatment. The Shapiro-Wilk normality test showed that the data were not normally distributed, so the hypothesis was tested using the non-parametric Wilcoxon Signed Ranks Test. The analysis revealed a significance value of 0.000 (<0.05) and a Z-value of -3.775. This proves that there is a significant effect of applying the role playing method on students' speaking skills. In conclusion, the role playing method is effective as a strategy to improve elementary school students' speaking abilities. Keywords: Role Playing, Speaking Skills, Social Studies Learning.